Unconventional secretion of synuclein‐γ promotes tumor cell invasion. (10th October 2014) - Liu, Caiyun; Qu, Like; Lian, Shenyi; Tian, Zhihua; Zhao, Chuanke; Meng, Lin; Shou, Chengchao
Abstract : Synuclein‐γ (SNCG) is a chaperone protein and exists mainly in the cytoplasm. SNCG confers chemoresistance, and is a potential unfavorable biomarker for multiple types of cancer. Our previous work demonstrated that SNCG could be detected in the serum of cancer patients and the medium of cultured cancer cells, but the mechanism of SNCG secretion and its biological roles are unknown. Here, we showed that SNCG levels in the culture medium were positively correlated with cancer cell densities and the concentrations of fetal bovine serum added. SNCG secretion was unaffected by brefeldin A, an inhibitor of the classic protein transport pathway, but was antagonized by exosome inhibitor, lysosome inhibitor, ABC transporter inhibitor, and phosphatidylinositide 3‐kinase inhibitor, and knockdown of Rab27a. Ultracentrifugation fractionation revealed that intracellular SNCG was present as both free and vesicle‐associated forms, but that the extracellular SNCG was mainly free. The results of reciprocal coimmunoprecipitation experiments showed an interaction between SNCG and flotillin‐2, a marker of exosomes and lipid rafts. Moreover, we demonstrated that SNCG, both secreted from tumor cells and exogenously added, markedly promoted cancer cell migration and invasion, but had no effect on noncancerous cells. These findings suggest that SNCG is actively secreted by cancer cells via an unconventional secretion pathway and contributes to aggressive phenotypes of cancer cells. Structured digital abstract: Flotillin-2  physically interacts  with SNCG  by anti bait coip  (1,  2 ). Abstract : We report Synuclein‐γ (SNCG), a cytoplasmic protein, can secrete from cancer cells by exosome, secretory lysosome, and ABC transporter pathways. Additionally, its secretion depends on phosphatidylinositide 3‐kinase (PI3K) signaling. SNCG exists as both free and vesicle‐associated forms and interacts with Flotillin‐2. Extracellular SNCG promotes cancer cell migration and invasion, but has no effect on non‐cancerous cells.